CODE MIXING IN SELEB ENGLISH VIDEO CONTENT ON YOUTUBE - Wulandari, Tri; Valiantien, Nita Maya; Asanti, Chris (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
Code mixing usage can easily be found in everyday use for public communication, both in formal and non-formal contexts. In this millennial era, code mixing is commonly found in social media, particularly in YouTube. In Indonesia, the video creators or usually called as YouTubers sometimes mix their languages, and the commonly mixed languages used are Indonesian and English. Considering the previously mentioned phenomena, this research focuses on analyzing and observing the code mixing on YouTube entitled Seleb English by Sacha Stevenson. The researchers applied qualitative method because the data of this study were described by looking at the reality that occurred in the form of oral language. What is more, the data were then analyzed and interpreted objectively in the forms of words and languages. The purposes of this study were to find out the types of code mixing, this was answered by using Muysken’s theory (2000) and in order to determine the reasons of using code mixing, Hoffmans’s theory (1991) was applied. Based on the result of this research, it is found that there are three types of code mixing such as insertion, alternation, and congruent lexicalization. In addition, the researchers found that the reasons of using code mixing in Seleb English are talking about a particular topic, being emphatic about something (express solidarity), interjection, repetition used for clarification, and expressing group identity. Therefore, code mixing as a language phenomenon is not only found in real life, but also in digital context.